PERSEPSI GURU IPA TERPADU TERHADAP PEMBELAJARAN DARING DENGAN MENGGUNAKAN APLIKASI WHATSAPP DI SMP NEGERI KECAMATAN BATHIN VIII KABUPATEN SAROLANGUN - Ria Andrianis; Rozana Zuhri; Andriyanto (BIOCOLONY, 2021)
The COVID-19 pandemic has caused a number of schools and colleges to temporarily close. Learning activities in a number of schools are carried out through online mode (in the network) and eliminate face-to-face learning. The implementation of online learning in Indonesia, including in Sarolangun Regency, especially in the State Junior High School, Kecamatan Bathin VIII, conducts online learning. This study aims to determine the perception of Integrated Science teachers towards online learning by using the WhatsApp application at the State Junior High School, Kecamatan Bathin VIII, Kabupaten Sarolangun, Provinsi Jambi. This type of research is a quantitative descriptive study with a survey method. Data collection techniques in this study used questionnaires, interviews, observation, and documentation instruments. The population in this study amounted to 10 junior high school teachers in Kecamatan Bathin VIII, Kabupaten Sarolangun, Provinsi Jambi. Based on the overall results of the study, it was concluded that the perception of Integrated Science teachers towards online learning by using the WhatsApp application at the State Junior High School, Kecamatan Bathin VIII, Kabupaten Sarolangun, Provinsi Jambi, was in the good category. With practicality 71.88% good category, ability to use the internet and communication tools in learning 78.12% good category, understanding of the use of whatsapp applications in delivering learning materials 78.89% good category, giving lesson assignments 83.13% good category and evaluating lesson assignments 69.17% in the poor category. So it can be said that the perception of Integrated Science teachers towards online learning at SMP Negeri VIII is in good category. Keywords: Perception of online learning, Integrated Science Teacher